21st century climate change: where has all the geomorphology gone?. Issue 1 (22nd November 2012) - Lane, Stuart N.
ABSTRACT This Commentary draws together recently published work relating to the relationship between climate change and geomorphology to address the surprising observation that geomorphic work seems to have had little impact upon the work of the Intergovernmental Panel for Climate Change. However, recent papers show that methodological innovation has allowed geomorphological reconstruction over timescales highly relevant to late 20th century and 21st century climate change. In turn, these and other developments are allowing links to be made between climatic variability and geomorphology, to begin to predict 'geomorphic futures' and also to appreciate the role that geomorphic processes play in the flux of carbon and the carbon cycle. Copyright © 2012 John Wiley & Sons, Ltd.